A familial analysis of aggressive periodontitis - clinical and genetic findings - Nibali, L.; Donos, N.; Brett, P. M.; Parkar, M.; Ellinas, T.; Llorente, M.; Griffiths, G. S. (Journal of periodontal research, 2008)
Background and Objective:  Family history is a primary diagnostic criterion for current classification of aggressive periodontitis (AgP). However, results of previous studies have shed controversy over the degree of familiarity of AgP and its possible inheritance mechanisms. The aims of this study were to estimate the percentage of affected relatives of AgP individuals, to analyse the disease phenotypes in relatives and to explore the distributions of genetic polymorphisms of interleukin‐6 (IL‐6) in AgP patients and in diseased and healthy relatives. Material and Methods:  Patients with AgP were clinically examined and asked to provide relatives for examination. First‐degree relatives were clinically and radiographically diagnosed. Blood samples were collected, DNA was extracted and analysis of single nucleotide polymorphisms of IL‐6 (at positions −174, −1363 and −1480) by polymerase chain reaction was performed in patients and relatives. Results:  Fifty‐five AgP patients provided relatives for examination. A total of 100 first‐degree relatives were assessed and 10 of them (10%) were found to have AgP. All relatives diagnosed with AgP had the same disease as the corresponding proband (localized AgP/localized AgP or generalized AgP/generalized AgP). The same IL‐6 genotypes (−174 GG, −1480 CC) previously associated with AgP showed a tendency for association with AgP in relatives. Conclusion:  This pilot study confirmed a relatively high risk for relatives of AgP patients to have AgP (10%). Genetic polymorphisms in the IL‐6 gene may have an impact in aetiopathogenesis. This study provides a sample size calculation for a novel study design using healthy relatives as control subjects.